2013
DOI: 10.1111/pcn.12086
|View full text |Cite
|
Sign up to set email alerts
|

Review of mental‐health‐related stigma in Japan

Abstract: The aim of this study is to understand the nature and characteristics of mental‐health‐related stigma among Japanese people. We searched relevant studies in English or Japanese published since 2001 using MEDLINE and PsycINFO, and found 19 studies that examined mental‐health‐related stigma in Japan. Regarding knowledge about mental illness, reviewed studies showed that in the Japanese general population, few people think that people can recover from mental disorders. Psychosocial factors, including weakness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
158
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(168 citation statements)
references
References 48 publications
6
158
3
1
Order By: Relevance
“…Responses to the items are rated as 'agree strongly', 'agree slightly', 'neither agree nor disagree', 'disagree slightly', 'disagree strongly' and 'don't know'. For each item, a score of 5 was allocated for strong agreement, while a score of 1 was assigned to strong disagreement (score range of the subscale: [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The response option 'don't know', is coded as neutral (i.e., 3).…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses to the items are rated as 'agree strongly', 'agree slightly', 'neither agree nor disagree', 'disagree slightly', 'disagree strongly' and 'don't know'. For each item, a score of 5 was allocated for strong agreement, while a score of 1 was assigned to strong disagreement (score range of the subscale: [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The response option 'don't know', is coded as neutral (i.e., 3).…”
Section: Instrumentmentioning
confidence: 99%
“…9,10 Japanese studies in particular have rarely reported discrimination towards people with mental health problems, although Japanese adults and children both tend to hold more negative attitudes than individuals in other countries. 11,12 This lack of research evidence on discrimination could be attributed to the absence of scales to accurately assess individuals' behavior towards people with mental health problems. In fact, most of the scales that assess such stigma focus only on others' knowledge of mental health issues and attitudes towards people with mental health problems.…”
mentioning
confidence: 99%
“…Huge potential for the regional revitalization in the declining society of Japan. Still in Japan, disability is considered the limitation and one of the students in his report explained how inspiring it was to see people with disabilities working in café and providing services for the customers in Kanazawa: ìThe 2013 study entitled ìReview of Mental-Health-Related stigma in Japanî (Ando, Yamaguchi, Aoki & Thornicroft, 2013) states that 61 % of employers would not consider employing someone with a history of mental health illness. And only 20 % of psychological professionals believed that people struggling with mental illness do not require hospitalization to recover.…”
Section: Academic Institution and Proper Education For Allmentioning
confidence: 99%
“…Under this condition, Japanese people have minimal contact with MIPs and do not have an adequate understanding of their disabilities 6) . As a result, they had more negative attitudes toward MIPs than people of other nations [7][8][9] . In addition, mental health care services have remained insufficient in Japan 10) , and their readmission rate is still high 11) .…”
mentioning
confidence: 99%